Pengaruh Penggunaan Ekstrak Daun Balakacida (Chromolaena odorata) sebagai Agen Hemostatik Pasca Pencabutan pada Tikus Wistar (Rattus norvigicus) - Muhammad Fajrin Wijaya; Ardian Jayakusuma Amran; Taufan Lauddin; Sulfiana Sulfiana; Nurul Annisa Syarifuddin (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Tooth extraction is a procedure to remove a tooth from its alveolar bone socket. The causes for tooth extraction include caries, periodontitis, fractures, impacted teeth, the need for orthodontic treatment, and persistent primary teeth. Post-extraction bleeding is the most common complication that occurs. Hemostasis is a mechanism to stop bleeding from blood vessels to prevent excessive blood loss when an injury occurs, ensuring that blood continues to flow smoothly. In stopping bleeding, there are three processes involved: vasoconstriction (the narrowing of blood vessels), platelet activity, and the activity of blood clotting factors. Bleeding time is the time interval from when blood exits the blood vessel until the bleeding stops. The normal range for bleeding time is 1 to 3 minutes. Balakacida leaves contain active compounds including alkaloids, tannins, flavonoids, saponins, and phenolics. To determine the effect of Balakacida leaf extract (Chromolaena odorata) as a hemostatic agent following tooth extraction in Wistar rats (Rattus norvegicus). This study uses an experimental method with a Post-Test Only Control Group Design. The samples used in this research are male Wistar rats (Rattus norvegicus), aged 2–3 months, weighing between 200–250 grams. The research data were processed and analyzed using the One-Way ANOVA test. The results showed that treatments at concentrations of 10%, 20%, and 30% were able to significantly accelerate bleeding time compared to the control group. The administration of Balakacida leaf extract is effective as a hemostatic agent following tooth extraction in Wistar rats.